Sea surface temperature retrieval based on simulated space-borne one-dimensional multifrequency synthetic aperture microwave radiometry - Guo, Chaogang; Ai, Weihua; Liu, Maohong; Feng, Mengyan; Qiao, Junqi; Hu, Shensen (Frontiers in Environmental Science, 2022)
Space-borne one-dimensional multifrequency synthetic aperture microwave radiometer (1D-MSAMR) offers new possibilities for detecting high spatial resolution sea surface temperature (SST). To achieve higher SST retrieval accuracy, an SST retrieval algorithm called "two-step retrieval algorithm" is proposed based on the multiple linear regression algorithm. In this paper, we investigate the SST retrieval accuracy of 1D-MSAMR based on simulation experiments. This study assumed that the frequencies of the 1D-MSAMR are 6.9,10.65,18.7,23.8 and 36.5 GHz and all frequencies work in a dual polarization manner (vertical and horizontal polarization). We use an ocean-atmosphere microwave radiation brightness temperature model and 1D-MSAMR simulator to simulate the measured brightness temperature based on the WindSat data provided by the Remote Sensing Systems (RSS). Then, a multiple linear regression algorithm and the two-step retrieval algorithm are developed to retrieve the SST within the incidence angle range of 0°-65°. The results show that the SST retrieval errors of the two SST retrieval algorithms decrease with the increase of incidence angle. The two-step retrieval algorithm has higher retrieval accuracy, especially in the low incidence angle. The average retrieval accuracy of the two-step retrieval algorithm is about 0.3K higher than that of the multiple linear regression algorithm. Retrieval error of the two-step retrieval algorithm is less sensitive to the measurement error of the 6.9 GHz frequency than the multiple linear regression algorithm.